AB0466 EFFICACY AND SAFETY OF INFLIXIMAB-BIOSIMILAR IN TAKAYASU ARTERITIS (TAKASIM): A MONOCENTRIC, OBSERVATIONAL, PROSPECTIVE, OPEN-LABEL STUDY. (2nd June 2020) - Campochiaro, C.; Tomelleri, A.; Sartorelli, S.; De Luca, G.; Sembenini, C.; Cavalli, G.; Mapelli, P.; Picchio, M.; Papa, M.; Baldissera, E.; Dagna, L.
Abstract : Background: Treatment of Takayasu arteritis (TA) is mainly based on steroids, but, in approximately 50% of patients, disease-modifying antirheumatic drugs(DMARDs) are required. Objectives: To evaluate efficacy and safety of IFX-biosimilar in TA patients. Methods: Both bDMARD-naïve and IFX-O treated patients were eligible. Primary endpoint was the number of patients with active disease as assessed by magnetic resonance angiography(MRA), 18FDG PET/CT, ITAS2010 and ITAS-ESR/CRP at month 6. Secondary endpoints were safety and tolerability, number of patients with active disease at month 12, quality of life. Non-parametric statistic tests were used. Results: Twenty-three patients(21 female) were recruited. At baseline, mean age was 43.8±14.4 years and mean disease duration 95.5±61.3months. Two patients were IFX-O-naïve. Mean time on IFX-O was 51.5±37.9 months. Four patients had been previously treated with other biologics(tocilizumab, 3; adalimumab, 1). Twenty-one patients(91.3%) were on concomitant steroids(mean dose, 4.8±2.0 mg daily) and 82% on concomitant csDMARDs, kept unchanged throughout the study. At baseline, 4 patients(17%) were classified as active according to ITAS2010, ITAS-ESR, and ITAS-CRP; mean HAQ was 3.48±5.26. Over the study period two patients dropped out the study because of poor disease control (1 at month 3 and 1 at month 6). PET/CT was not available for one patient who was on lactation during the study period and 1 patient refused to undergo imaging re-evaluation. At month 6, MRA was available for 21 patients: it was stable in 11(52%), improved in 5(24%), worsened in 5(24%). PET/CT was available for 20 patients: it was negative in 12(65%), improved although still positive in 3(16%), stable in 1(5%), worsened in 3(16%). At month 6, among 22 patients, 4(18%) were clinically active according to ITAS2010, ITAS-ESR and ITAS-CRP; mean steroid dose was significantly lower compared to baseline(4.2±2.0 mg daily, p=0.009); HAQ didn't significantly change(mean, 3.35±6.59, p=0.357). At month 12, MRA was available for 20 patients. It was stable in 9 patients(45%), improved in 8 (40%), worsened in 3(15%). PET/CT was available for 19 patients: it was negative in 14(74%), improved although still positive in 2(10%), stable in 3(10%), worsened in 1(5%). At month 12, 3 patients(14%) were active according to ITAS2010 and 2(9%) according to ITAS-ESR and ITAS-CRP; mean steroid dose was significantly lower compared to baseline(3.4±2.56 mg daily, p=0.034); HAQ didn't significantly change(mean, 3.84±6.34, p=0.919). Nine patients(39%) experienced low-grade side effects related to TNFα-blockade (6, herpes reactivation; 3, urinary tract infection; 1 gastroenteritis). No IFX-B therapy modification was required. Conclusion: Our study suggests that IFX-B is effective and safe both in IFX-O switch and IFX-O naïve TA patients. Disclosure of Interests: Corrado Campochiaro Speakers bureau: Novartis, Pfizer, Roche, GSK, SOBI, Alessandro Tomelleri: None declared, Silvia Sartorelli: None declared, Giacomo De Luca Speakers bureau: SOBI, Novartis, Celgene, Pfizer, MSD, Camilla Sembenini: None declared, Giulio Cavalli Speakers bureau: SOBI, Novartis, Pfizer, Paola Mapelli: None declared, Maria Picchio: None declared, Maurizio Papa: None declared, Elena Baldissera Speakers bureau: Novartis, Pfizer, Roche, Alpha Sigma, Sanofi, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI